EXPERIMENTAL INVESTIGATION ON ETHYLENETETRAFLUOROETHYLENE INNER COATED PIPE FOR WAX DEPOSITON - MOMBEKOV, BAGDAT (2015)
The paraffinic deposition on the inner surface of subsea pipelines presents a costly problem in the production and transportation of oil. The problem is caused by unprocessed or partly processed waxy crude oil transported through the cold subsea pipeline over a long distance and can reduce the pipe diameter and flow through the pipe. Paraffinic deposition simulators cannot accurately account for factors such as pressure drop, flow rate, surface roughness, surface energy of the pipe, wettability of pipe wall as well as temperature differential between the fluid and the surrounding. The present study therefore attempted to evaluate the effects of a novel polymer Ethylene- TetraFluoroEthylene (ETFE) coated pipe at different temperatures and flow rates on the rate of paraffinic deposition. The performance was compared to Steel and PVC pipes. Characterizations of the crude oil were performed based on ASTM methods.